Neonatal brain injuries in England: population-based incidence derived from routinely recorded clinical data held in the National Neonatal Research Database. Issue 4 (22nd October 2017) - Gale, Chris; Statnikov, Yevgeniy; Jawad, Sena; Uthaya, Sabita N; Modi, Neena
Abstract : Objective: In 2015, the Department of Health in England announced an ambition to reduce 'brain injuries occurring during or soon after birth'. We describe the development of a pragmatic case definition and present annual incidence rates. Design: Retrospective cohort study using data held in the National Neonatal Research Database (NNRD) extracted from neonatal electronic patient records from all National Health Service (NHS) neonatal units in England, Wales and Scotland. In 2010–2011, population coverage in the NNRD was incomplete, hence rate estimates are presented as a range; from 2012, population coverage is complete, and rates (95% CIs) are presented. Rates are per 1000 live births. Setting: NHS neonatal units in England. Patients: Infants admitted for neonatal care; denominator: live births in England. Main outcome measure: 'Brain injuries occurring at or soon after birth' defined as infants with seizures, hypoxic-ischaemic encephalopathy, stroke, intracranial haemorrhage, central nervous system infection and kernicterus and preterm infants with cystic periventricular leucomalacia. Results: In 2010, the lower estimate of the rate of 'Brain injuries occurring at or soon after birth' in England was 4.53 and the upper estimate was 5.19; in 2015, the rate was 5.14 (4.97, 5.32). For preterm infants, the population incidence in 2015 was 25.88 (24.51, 27.33) and 3.47 (3.33, 3.62) for term infants. Hypoxic-ischaemic encephalopathy was the largest contributor to term brain injury, and intraventricular/periventricular haemorrhage was the largest contributor to preterm brain injury. Conclusions: Annual incidence rates for brain injuries can be estimated from data held in the NNRD; rates for individual conditions are consistent with published rates. Routinely recorded clinical data can be used for national surveillance, offering efficiencies over traditional approaches.